Gina Pane and Krzysztof Jung: Queer Love in European Performance Art of the 1970s - Paweł LESZKOWICZ (Sztuka i Dokumentacja)
This essay examines how performance art and counterculture in the 1970s opened up the possibility for two queer action/body artists to express an alternative vision of love in its plurality. The French-Italian lesbian artist Gina Pane and the Polish gay artist Krzysztof Jung performed same-sex love, pleasure, and suffering on both sides of the Iron Curtain in Cold War Europe. In their unique pioneering body art, they examined sexual identities, embodied subjectivity, personal emotions, and artistic involvement in human freedom at a time of dramatic social transformation in both Eastern and Western European context. I will analyze ground-breaking performances by Pane and Jung from the 1970s in order to look comparatively at queer art and performance of the time, and also question the way European art history is divided hierarchically into cultural centers and peripheries. Gina Pane is a well-known star of European body art of the 1970s; Krzysztof Jung as a Polish artist from the former communist Eastern Block almost disappeared from mainstream art history. The significant actions of Pane were performed in Italy, in the European South, an area marginalized in the canonical story of post-war modern art.